2011
DOI: 10.1002/mc.20770
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonoyl ethanolamide (AEA)‐induced apoptosis is mediated by J‐series prostaglandins and is enhanced by fatty acid amide hydrolase (FAAH) blockade

Abstract: The endocannabinoid arachidonoyl ethanolamide (AEA) is a potent inducer of tumor cell apoptosis however its mechanism of cytotoxicity is unclear. A previous report from our laboratory showed that AEA induced cell death in a COX-2-dependent manner and in this report our data indicate that AEA-induced apoptosis is mediated by COX-2 metabolic products of the J-series. In experiments conducted with JWF2 keratinocytes which overexpress COX-2, AEA caused a concentration-regulated increase in J-series prostaglandin p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 41 publications
4
31
0
Order By: Relevance
“…In addition and in contrast to the traditional view implying a protumorigenic function of COX-2 ( 19,20 ), overexpression of COX-2 decreased proliferation and increased apoptosis of osteosarcoma cells ( 21 ), and it protected rather than sensitized animals to experimental skin tumor development ( 22 ). In line with these fi ndings, COX-2 upregulation has emerged as a proapoptotic mechanism shared by various antitumorigenic compounds (23)(24)(25)(26)(27)(28)(29)(30).…”
mentioning
confidence: 71%
“…In addition and in contrast to the traditional view implying a protumorigenic function of COX-2 ( 19,20 ), overexpression of COX-2 decreased proliferation and increased apoptosis of osteosarcoma cells ( 21 ), and it protected rather than sensitized animals to experimental skin tumor development ( 22 ). In line with these fi ndings, COX-2 upregulation has emerged as a proapoptotic mechanism shared by various antitumorigenic compounds (23)(24)(25)(26)(27)(28)(29)(30).…”
mentioning
confidence: 71%
“…Cyclooxygenase 2 is involved in the degradation of AEA in the brain [43] and this pathway may be prominent in FAAH -/-mice. The enhanced level of prostamides [43] in the mouse brain and possibly prostaglandins (measured in keratinocytes) [44] due to this alternative degradation pathway and the induction of arachidonic acid pathway due to the enhanced AEA levels [45] together can lead to an elevated chronic pro-inflammatory signaling in FAAH -/-animals.…”
Section: Discussionmentioning
confidence: 97%
“…Recently we showed that AEA-induced cytotoxicity was mediated by the production of proapoptotic, J-series prostaglandins in tumorigenic keratinocytes that overexpress COX-2 (Van Dross, 2009;Kuc et al, 2012). In addition, resistance to AEA-induced cytotoxicity was observed in non-tumorigenic keratinocytes with low basal COX-2 expression however, these cells underwent cell death when transfected with an expression plasmid containing COX-2.…”
Section: Endocannbinoids and Cycloxygenase-2 (Cox-2) In Cancermentioning
confidence: 99%